If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5a + -7) = (6a + 5) Reorder the terms: (-7 + 5a) = (6a + 5) Remove parenthesis around (-7 + 5a) -7 + 5a = (6a + 5) Reorder the terms: -7 + 5a = (5 + 6a) Remove parenthesis around (5 + 6a) -7 + 5a = 5 + 6a Solving -7 + 5a = 5 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. -7 + 5a + -6a = 5 + 6a + -6a Combine like terms: 5a + -6a = -1a -7 + -1a = 5 + 6a + -6a Combine like terms: 6a + -6a = 0 -7 + -1a = 5 + 0 -7 + -1a = 5 Add '7' to each side of the equation. -7 + 7 + -1a = 5 + 7 Combine like terms: -7 + 7 = 0 0 + -1a = 5 + 7 -1a = 5 + 7 Combine like terms: 5 + 7 = 12 -1a = 12 Divide each side by '-1'. a = -12 Simplifying a = -12
| 19540-23150= | | Y-5=23 | | -9+x/4=-7 | | 5k=12+2k | | 170*11= | | x/10+4=5 | | -7+4x=-15 | | 7X-(3X+5)=2X-39 | | -12x+4=100 | | 1.2x-0.5=20 | | 6n+24=4n | | -12+4=100 | | (z^2+5z+8)(z^2+2z+6)=50000000000000000000000 | | 4(1/2)-9=-9 | | 4+4N=2N+6 | | 11p=54+5p | | 4x^2-33x+31=-8x+6 | | X+5=-x-13 | | 4+N=2N+6 | | 3(1)-5y=15 | | 2.5x+6y=38 | | 2-X=4X+17 | | x^2+15x-33=6x+3 | | x*x+5x-12=22 | | 3T-4=28-T | | 2y+2-5=7 | | 2x+1=9/(x+2) | | 3a-12=7a | | 4d^2= | | (2x^3y)^4/3x^2(4x^5y^2) | | 8f-3q=11f | | 3a^3-24a^2+48=0 |